Reorientasi Misteri Shalat Subuh dalam Perspektif Hadis - Ardhy Sulaiman (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2018)
Fajr prayer is one of the five obligatory prayers that have exceptional peculiarities and virtues. It was at this point that the turn of night and day began. At this very moment, the night and afternoon angels change duties. Fajr prayers in congregation is a heavy mandatory worship to be performed, they do not know that in the dawn prayer there is a great virtue, except by people who really sincerely expect the pleasure of Allah swt. Its execution time on the blind that makes people lazy to do it. Based on the above background, the formulation of the problem in this thesis is: 1). How does the nature of the Subuh prayers congregate according to the tradition ?, 2). How is the quality of traditions related to the virtue of Fajr prayers in congregation ?. 3). How is the virtue of Fajr praying in congregation ?. The purpose of this research are: 1). To know the nature of dawn prayer in congregation of hadith. 2). To know the quality of the traditions related to the virtue of Fajr prayers in congregation. 3). To know the virtue of Fajr prayers in congregation in the view of the clergy. The method used in this thesis is library research method which is collecting data from Hadith books of Bukhārῑ, Muslim, Ibn Māzah, Abū Dāud, Tirmiẓi dan Ad-Dārimῑ and seeking information with the help of interview, then the data is analyzed by using method criticism of hadith, that is criticism of sanad and matan by using jarḥ wa ta'dil every perawinya. The results of this study, as follows: Fajr prayer is a mandatory prayer performed on the morning at dawn arrived, dawn prayer is also a severe worship to be executed except by people who really sincere expect the pleasure of Allah swt. Hadiths of the Prayers of the Fajr Prayers which the author has meticulously qualified ṣaḥiḥ such as the hadith narrated by Bukhārῑ, the hadith of the Muslim narrative, the hadith of Ahmad's narration, and the hadith narrated by ad-Darimi, but the authors found the traditions of the high-quality dawn prayers such as Ibn Mazah and Tirmiżi. The virtue of the Fajr prayers according to the views of ulema bahwasannya prayers in which there is a great reward that does not exist in other fardu prayers, such as getting a guarantee of the hereafter of Allah swt.